E-Commerce Sales System Based Mobile Android (Case Study: PT.Makmur Cipta Sejahtera) - Agung Kurniawan Toing; Ardie Halim Wijaya (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2019)
With the passage of the sales process manually which is less efficient and less effective in PT. Makmur Cipta Sejahtera, it needs a program to support the efficiency and effectiveness of the sales process. The process of ordering goods that still use manual methods to use mail order goods, make the authors design and create an Android-based sales program. This program will be addressed to PT. Makmur Cipta Sejahtera entitled